Enhancing engagement in HIV care among adolescents and young adults: A focus on phone-based navigation and relationship building to address barriers in HIV care. - Harriet Fridah Adhiambo; Chanda Mwamba; Jayne Lewis-Kulzer; Sarah Iguna; Gladys Moraa Ontuga; Dorothy Imbuka Mangale; Everlyne Nyandieka; James Nyanga; Isaya Opondo; Joseph Osoro; Lina Montoya; Edwin Nyagesoa; et al. (PLOS Global Public Health)
Structural, psychological, and clinical barriers to HIV care engagement among adolescents and young adults living with HIV (AYAH) persist globally despite gains in HIV epidemic control. Phone-based peer navigation may provide critical peer support, increase delivery flexibility, and require fewer resources. Prior studies show that phone-based navigation and automated text messaging interventions improve HIV care engagement, adherence, and retention among AYAH. However, little is known about AYAH experiences utilizing electronic phone-based peer navigation and automated text messaging (E-NAV). We assessed the experiences of AYAH receiving phone-based peer navigation to address barriers to HIV care engagement and viral suppression. We purposefully selected participants randomized to E-NAV within the Adapt for Adolescents in Kisumu, Kenya, and conducted 20 in-depth interviews. Interviews were conducted by a trained qualitative researcher between October and December 2021 and explored topics such as health-seeking and care experiences, E-NAV acceptability and benefits, and the client-navigator relationship. The interviews were audio-recorded and transcribed. We then applied inductive and deductive coding, followed by thematic analysis. Overall, participants found E-NAV acceptable in regard to content and frequency-particularly the opportunity to select a preferred time for calls/text messages, including evenings and weekends. They found the tone of navigator calls and messages friendly, supporting relationship building. Further, AYAH-navigator relationships were described as fraternal, client-focused, and confidential, which supported a personal connection and trust. Reported E-NAV benefits included adherence and appointment reminders, increased knowledge about HIV care, and strategies to address HIV stigma. Electronic navigation is a promising method for youth peer navigation because it optimizes reach (both in time and space) for youth that have severe constraints on both while preserving the ability to create a rapport and a relationship with patients.